Answer:
[tex]\dfrac13y-\dfrac75x+\dfrac23-\dfrac23y-\dfrac49[/tex]
Step-by-step explanation:
[tex]-\dfrac23y-\dfrac35x+\dfrac29-\dfrac45x+\dfrac13y[/tex]
Collect like terms:
[tex]\implies -\dfrac23y+\dfrac13y-\dfrac35x-\dfrac45x+\dfrac29[/tex]
Combine like terms:
[tex]\implies -\dfrac13y-\dfrac75x+\dfrac29[/tex]
[tex]\dfrac13y-\dfrac75x+\dfrac23-\dfrac23y-\dfrac49[/tex]
Collect like terms:
[tex]\implies \dfrac13y-\dfrac23y-\dfrac75x+\dfrac23-\dfrac49[/tex]
Combine like terms:
[tex]\implies -\dfrac13y-\dfrac75x+\dfrac29[/tex]
Therefore, [tex]\dfrac13y-\dfrac75x+\dfrac23-\dfrac23y-\dfrac49[/tex] is equivalent to [tex]-\dfrac23y-\dfrac35x+\dfrac29-\dfrac45x+\dfrac13y[/tex]